2018
DOI: 10.5005/jp-journals-10024-2387
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Pulp Stones in Patients following Orthodontic Treatment

Abstract: Aim: The present study aimed to find prevalence of pulp stones in known South Indian orthodontic patients and to find correlation between pulp stones and patients who underwent orthodontic treatment as well as to reveal any differences due to gender, tooth type, and dental arches. Materials and methods:The present retrospective study was carried out among 200 patients who underwent nonextraction orthodontic treatment. Maxillary and mandibular first and second premolar and molar teeth were selected for the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Ertas et al assessed patients who had undergone nonextraction orthodontic treatment and concluded that pulp stone prevalence sharply rose (2.2%) in the radiographs taken after the treatment [25]. Another similar study reported an overall 4% increase in cases after the commencement of orthodontic treatment [26]. Their results were similar to the current study; however, our rate of increase was higher which might be due to the fact that we did not exclude the patients who had undergone extraction orthodontic treatment.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ertas et al assessed patients who had undergone nonextraction orthodontic treatment and concluded that pulp stone prevalence sharply rose (2.2%) in the radiographs taken after the treatment [25]. Another similar study reported an overall 4% increase in cases after the commencement of orthodontic treatment [26]. Their results were similar to the current study; however, our rate of increase was higher which might be due to the fact that we did not exclude the patients who had undergone extraction orthodontic treatment.…”
Section: Discussionsupporting
confidence: 75%
“…In this study similar to several studies, there was no statistically discernible difference in the incidence of pulp stones before orthodontic treatment among genders [25][26][27]; in contrast, Afsari et al, in a retrospective cross-sectional study, investigated the number of pulp stones prior and following to orthodontic treatment using radiographs of patients undergoing orthodontic and nonorthodontic treatment. They found a significant relationship between gender and pulp stones because females had considerable changes in the number of pulp stones [30].…”
Section: Discussionsupporting
confidence: 72%
“…The application of forces during orthodontic treatment can induce pulpal calcifications, characterized by the deposition of mineralized tissue in the pulp cavity space ( 3 , 4 ). The two main morphologies of pulpal calcifications include pulpal stones or nodes and diffuse calcifications.5 Other factors known to contribute to the formation of pulpal calcifications include dental trauma, bruxism, carious lesions, occlusal imbalance, and increasing age ( 2 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The obliteration of the pulp cavity, or the presence of pulp nodes, represents challenges for locating, accessing, and instrumenting root canals. Accidents such as instrument deflection and fracture can happen, and patency is often not possible during biomechanical preparation ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the exact cause behind the development of pulp stones is still uncertain. However, several factors have been suggested to contribute to their formation, including calcification of the pulp, orthodontic tooth movement, aging, periodontal disease, deep caries, calcifying nanoparticles, bacterial infection, systemic diseases, restorations, and genetic predisposition [12][13][14][15]. A significant association has been observed between pulp stones and systemic diseases, such as diabetes, heart disease, cholelithiasis, and renal lithiasis [16].…”
Section: Introductionmentioning
confidence: 99%